CC2: Defending Hybrid Worm on Mobile Networks with Two-Dimensional Circulation Control. (14th December 2019) - Yang, Hailu; Chen, Deyun; Sun, Guanglu; Ding, Xiaoyu; Xin, Yu
Abstract : As the hybrid worm can propagate by both personal social interactions and wireless communications, it has been identified as one of the most severe threats to the mobile Internet. This problem is expected to become worse with the boom of social applications and mobile services. In this work, we study the propagation dynamics of hybrid worms and propose a systematic countermeasure. The system maintains a set of community structure which describes the high-speed infection zone of worms and contains worm propagation by distributing the worm signature to the guard nodes selected from the periphery of each community. For those nodes that are geographically close but located in different communities, we evaluate the communication security between them based on the observed infection history and limit communications between insecure ones to avoid the worm spreading across communities. We also design an efficient worm signature forwarding strategy that enables most nodes in the network to reach an immune state before being infected by the worm. Extensive real-trace driven simulations verify the feasibility and effectiveness of the proposed methods.